ANALISIS KUALITAS PELAYANAN DENGAN METODE QUALITY FUNCTION DEPLOYMENT TERHADAP PENGUNJUNG PERPUSTAKAAN UNIVERSITAS SLAMET RIYADI SURAKARTA - Krisna Prabowo Herukusumo; Amin Wahyudi; Sunarso Sunarso (Universitas Slamet Riyadi, 2020)
The aim of the study was to examine the quality of services provided by the Slamet Riyadi Surakarta University Library with the viewpoint of users (users / members) with the Quality Function Deployment method of the House of Quality matrix which is a top priority. The quality measured here is in 5 service mixes, namely tangibles, reliability, responsiveness, assurance and empathy with the types of qualitative and quantitative data. The population in the study of active and registered students became members of the library from 2015 - 2018 which were taken to be used as samples and used purposive sampling and non probability sampling techniques. Instrument which is the priority of repairs with technical solutions according to the preparation of QFD methods sequentially starting from the main priorities, namely: neatness of the arrangement of the location of books, reading rooms, and interior design. This is indicated by the raw weight calculation contribution value and normalized raw weight which is used to show the amount of improvement in a criteria or customer need.